Effect of granite fly ash on mechanical properties of basalt and glass fiber reinforced polymer composite / Mohd Azrul Jaafar ... [et al.] - Jaafar, Mohd Azrul; Abdullah, Shahrul Azam; Jumahat, Aidah; Hashim, Ummu Raihanah; Muslim, Mohamad Asrofi; Raja Ahsan Sha, Raja Mazuir; Raymond Siew, Teng Loy (UiTM Press, 2024)
The granite processing industry generates a substantial volume of residual granite waste daily. This residue is collected through a filtration process during the drying and heating stages of concrete mixture production. Utilizing this residue, known as granite fly ash (GD), offers a promising avenue for mitigating adverse effects due to this waste material. The present study undertakes an experimental investigation into the potential utilization of granite fly ash as a filler to enhance the mechanical properties of basalt/glass composites (BFRC/GFRC). The research focuses on assessing the density and tensile characteristics of the developed fibre-reinforced polymer (FRP) composites. Composite samples were fabricated by incorporating GD at varying loadings, i.e., 1 wt.%, 3 wt.%, and 5 wt.%. The FRP laminates were produced using hand lay-up and vacuum silicon mold curing techniques. The outcomes show a slight increase in density, in which a maximum of 7% increment at 5 wt% of GD in BFRC. Meanwhile, tensile properties displayed significant enhancements, especially FRP with 3 wt.% GD content, for both BFRC and GFRC. Notably, the addition of 1 wt.% GD resulted in a 9% increase in tensile strength and a substantial 27% increase in modulus for the BFRC composite. In summary, the study underscores the advantageous influence of GD incorporation, particularly within the 1 wt.%, 3 wt.%, and 5 wt.%, on the mechanical properties of both BFRC and GFRC composites.